2010
DOI: 10.1007/s11095-010-0072-3
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer-Targeted Imaging Using Magnetofluorescent Polymeric Nanoparticles Functionalized with Bombesin

Abstract: These results demonstrate that the BBN conjugation to NAHis-GC nanoparticles improves their tumor accumulation in PC3-bearing mice in comparison to nanoparticles without BBN, suggesting that BC-NAHis-GC nanoparticles may be useful for prostate cancer imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Moreover, bombesin, a 14-amino acid peptide binding to the bombesin receptor, has been studied for therapy of gastric-releasing peptide receptor (GRPR)-positive tumors. Bombesin conjugated to N-acetyl histidinemodified GC nanoparticles were able to bind to prostate cancer cells (PC-3) overexpressing GRPR, and iron oxide-loaded nanoparticles could be applied as a probe for magnetic resonance imaging (MRI) [34]. [35].…”
Section: Active Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, bombesin, a 14-amino acid peptide binding to the bombesin receptor, has been studied for therapy of gastric-releasing peptide receptor (GRPR)-positive tumors. Bombesin conjugated to N-acetyl histidinemodified GC nanoparticles were able to bind to prostate cancer cells (PC-3) overexpressing GRPR, and iron oxide-loaded nanoparticles could be applied as a probe for magnetic resonance imaging (MRI) [34]. [35].…”
Section: Active Targetingmentioning
confidence: 99%
“…To assess biodistribution of nanoparticles, fluorescent images 146 J.Y. Yhee et al are acquired at various time points up to 72 h post-injection using various photon counting scanners such as eXplore Optix system [9,16], the IVIS Spectrum smallanimal in vivo imaging system [34], or Kodak Image Station 4000 MM [37]. Although the tumor-homing efficiency of the nanoparticles was somewhat differentiated according to the different characteristics of each nanoparticle, many studies demonstrated that chitosan-based nanoparticles were accumulated in tumors.…”
Section: Optical Imagingmentioning
confidence: 99%
“…Both passive targeting, through Enhanced Permeability and Retention (EPR) effect (Decuzzi et al, 2009), and active targeting (Lee et al, 2010a;Liang et al, 2010;Zheng et al, 2012) were exploited in the application of NPs. In the example of passive targeting (EPR effect), Kim and colleagues developed polymeric NPs containing the fluorogenic probe Cy5.5 and the dark quencher BHQ-312, linked together by a peptide sequence specific for a matrix metalloproteinase (MMP) for in vivo tumor imaging .…”
Section: In Vivo Optical Sensingmentioning
confidence: 99%
“…A Cy5.5 filter set (640 nm for excitation, 700 nm for emission) and a subtraction filter set (600-570 nm for excitation) were used for acquiring the in vivo images. The obtained images were analyzed using Living Image Software (Caliper Life Science) (24). All animal experiments were performed in accordance with the guidelines suggested by the Chonbuk National University Medical School Ethics Committee.…”
Section: Cellular Binding Studies Of Cmbp Conjugation To Ga-atp@spionsmentioning
confidence: 99%